2015
DOI: 10.1007/s10858-015-9912-0
|View full text |Cite
|
Sign up to set email alerts
|

Transverse relaxation dispersion of the p7 membrane channel from hepatitis C virus reveals conformational breathing

Abstract: The p7 membrane protein encoded by Hepatitis C virus (HCV) assembles into a homo-hexamer that selectively conducts cations. An earlier solution NMR structure of the hexameric complex revealed a funnel-like architecture and suggests that a ring of conserved asparagines near the narrow end of the funnel are important for cation interaction. NMR based drug-binding experiments also suggest that rimantadine can allosterically inhibit ion conduction via a molecular wedge mechanism. These results suggest the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…The pattern of amide proton exchange of p7(5a/EUH1480) in DPC was similar to that of p7(1b/J4) in Cyclofos-6, and the results are consistent with the exchange rates previously reported for p7(5a/EUH1480) in similar conditions 30 . Some regions, including the N- and C-termini, helix 1, and H17, exhibited higher exchange rates in p7(5a/EUH1480), which may be due to differences in hydrophobicity between the constructs: The regions including residues 13–20 and 53–58 are more hydrophobic in p7(1b/J4) than p7(5a/EUH1480) (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The pattern of amide proton exchange of p7(5a/EUH1480) in DPC was similar to that of p7(1b/J4) in Cyclofos-6, and the results are consistent with the exchange rates previously reported for p7(5a/EUH1480) in similar conditions 30 . Some regions, including the N- and C-termini, helix 1, and H17, exhibited higher exchange rates in p7(5a/EUH1480), which may be due to differences in hydrophobicity between the constructs: The regions including residues 13–20 and 53–58 are more hydrophobic in p7(1b/J4) than p7(5a/EUH1480) (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 90%
“…A recent NMR structure suggests a different arrangement of short helical segments of p7, predicting the formation of a binding pocket for rimantadine outside of the channel pore, where it acts as an allosteric inhibitor (23). An NMR-based determination of solvent accessibility confirmed this architecture of the p7 protein and the allosteric mechanism of rimantadine inhibition (28). The activity of p7 as an intracellular pH shunt is believed to be involved in critical steps of the viral replication cycle, controlling acidification of endosomes and virion-loaded particles, and promoting vesicle trafficking and assembly and release of virions (29).…”
Section: Introductionmentioning
confidence: 92%
“…Dev et al . performed relaxation dispersion measurement on p7 channel in DPC micelles using 2D CPMG TROSY–HSQC experiment at 600 and 700 MHz . They found that while most of the channel did not show relaxation dispersion, residues at the H1–H2 hinge (Phe19) and the narrow end of the cavity (Val7, Leu8) experienced chemical exchanges ( K ex ∼ 1000 ± 79 s −1 and ∼10% excited state).…”
Section: Allosteric Modulation Of Membrane Protein Dynamics By Ligandmentioning
confidence: 99%